Vital parameters of Holstein calves from birth to weaning. - Silva, Bruno Toledo; Henklein, Ariana; Marques, Raquel de Sousa; de Oliveira, Pamella Lorenci; Leite, Stephanie Blima Paulino; Novo, Sylvia Marquart Fontes; Baccili, Camila Costa; dos Reis, Juliana França; Gomes, Viviani (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Silva B.T., Henklein A., Marques R. De S., de Oliveira P.L., Leite S.B.P., Novo S.M.F., Baccili C.C., Reis J.F. & Gomes V. Vital parameters of Holstein calves from birth to weaning. [Parâmetros vitais de bezerros Holandeses do nascimento ao desmame.] Revista Brasileira de Medicina Veterinária, 38(3):299- 304, 2016. Departamento de Clínica Médica, Faculdade de Medicina Veterinária e Zootecnia, Universidade de São Paulo, Av. Prof. Dr. Orlando Marques de Paiva 87, São Paulo, SP 05508-270, Brasil. E-mail: brunotoledovet@hotmail.com The neonatal period is represented by the inability of newborns to adapt themselves to extra-uterine environment and execution of vital functions until then executed by the mother, such as thermoregulation, basic acid balance, cardiorespiratory functions, nutrition and development of the immune system. This study aimed to evaluate the physiological adaptations of Holstein calves during milk-feeding period (60 days). We selected 22 newborn Holstein male calves, born between the months of September to March (n = 18) and April to August (n = 4). Heart rate values (HR), respiratory rate (RR) were recorded daily for 60 days by semiotic technique of auscultation, and the rectal temperature (RT) was measured with the use of digital clinical thermometer. The daily results of the experiment were divided in periods of six days each (P1 to P10). The first week of postnatal life was marked by physiological changes related to the adaptation of cardiorespiratory functions of newborns, observing stabilization of HR and RR on subsequent periods, with few variations probably attributed to climate fluctuation (10 a 37ºC) of the calves’ rearing environment. These data demonstrated direct impact of extra-uterine adaptation period on physiological parameters of newborn calves.